РЕВОЛЮЦИЯ И РЕВОЛЮЦИОНЕРЫ В АЗЕРБАЙДЖАНСКОМ РОМАНЕ (1930-1955 гг.) (Eurasian Journal of Philology Science and Education, 2015)
Bolshevik revolution existence matters of the movementand development of the revolution were the main subject of thenew Azerbaijan novels of 1930-50 years. In fact, the mainheroes of those works of literature were the revolutionaries. Inthe article, the regard is expressed to the revolution andrevolutionary conceptions from the point of new social-literarythought, political-literary features of the very novels written inthe level of concrete demands of the socialist realism method isstated